Pyodine: an open, flexible reduction software for iodine-calibrated precise radial velocities - Heeren, Paul; Tronsgaard, René; Grundahl, Frank; Reffert, Sabine; Quirrenbach, Andreas; Pallé, Pere L. (Astronomy and astrophysics, 2023)
Context. Many telescopes use an iodine (I2) absorption cell to measure precise radial velocities (RVs), but their data reduction pipelines are all tailored to their respective instrumental characteristics and not openly accessible. Aims. For existing and future projects dedicated to measuring precise RVs, we have created an open-source, flexible data reduction software to extract RVs from échelle spectra via the I2 cell method. The software, called pyodine, is completely written in Python and has been built in a modular structure to allow for easy adaptation to different instruments. Methods. We present the fundamental concepts employed by pyodine, which build on existing I2 reduction codes, and give an overview of the software’s structure. We adapted pyodine to two instruments, Hertzsprung SONG located at Teide Observatory (SONG hereafter) and the Hamilton spectrograph at Lick Observatory (Lick hereafter), and demonstrate the code’s flexibility and its performance on spectra from these facilities. Results. Both for SONG and Lick data, the pyodine results generally match the RV precision achieved by the dedicated instrument pipelines. Notably, our code reaches a precision of roughly 0.69 m s−1 on a short-term solar time series of SONG spectra, and confirms the planet-induced RV variations of the star HIP 36616 on spectra from SONG and Lick. Using the solar spectra, we also demonstrate the capabilities of our software in extracting velocity time series from single absorption lines. A probable instrumental effect of SONG is still visible in the pyodine RVs, despite being a bit damped as compared to the original results. Conclusions. With pyodine we prove the feasibility of a highly precise, yet instrument-flexible I2 reduction software, and in the future the code will be part of the dedicated data reduction pipelines for the SONG network and the Waltz telescope project in Heidelberg.
Online veröffentlicht: 19. Juni 2023
Gesehen am 28.09.2023